Academic Identity of Higher Education in Building Competitive Advantage - Fauzan Adhim; Rina Sugiarti Dwi Gita; Intan Tri Novita Sari (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
Academic Identity is a reflection of reputation in higher education. Its existence is a driver of competitiveness and the realization of good governance. The reason is that academic Identity has competitive characteristics that distinguish universities from other institutions and can shape public perception. Internally, a strong and consistent identity becomes a strategic value for universities. It will be an attraction and bargaining tool for external stakeholders in the global competition of higher education. This research aims to find the formulation and application of the academic Identity of higher education institutions in building competitive advantage. Methodologically, this research uses a qualitative type with a case study approach. This research was conducted at PGRI Argopuro University Jember. Researchers use data collection techniques such as in-depth interviews, document reviews, and focus group discussions. Informants involved include representatives of the foundation board, Rector, Vice Rector, Head of Study Program in each faculty, Head of Unit and external stakeholders. The data analysis that researchers use is case study analysis, which includes data identification, reduction, coding, presentation and conclusion drawing. This research produces findings: (1) The academic identity formulation process includes Socio-historical extraction, Identification of values and norms, Preservation of local wisdom, Adaptation of science and technology and strategic partnerships. (2) The application of UNIPAR academic identity is realized in two managerial frameworks: First, through policies contained in the Strategic Plan, RIP and Curriculum. Second, the internalization process for the entire community is done through professional capacity-building programs. The theoretical implication of this research is to develop a model of branding higher education institutions (HEIs) that emphasizes service-based competitive advantage. The scientific facts researchers found that academic branding in higher education has a holistic basis, including socio-historical aspects of governance, as researchers have described in the discussion.